Pengaruh Penggunaan Media Sosial terhadap Pola Interaksi Sosial Remaja Perkotaan - Nurcholis Sunuyeko; Sari, Ike Dian Puspita (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
This study explores the shift in social interaction patterns among urban adolescents in Surabaya due to the massive penetration and domination of social media use. Employing a qualitative approach with an exploratory case study design, primary data collection was conducted through semi-structured in-depth interviews and non-participant observation involving 15 adolescents aged 15 to 18 years. The data were then analyzed using thematic analysis techniques. The results reveal four main findings. First, the disruption of the communal essence in the local tradition of "cangkrukan", which is now reduced to a mere physical gathering without deep verbal interaction. Second, the high frequency of computer-mediated communication is proven to only create a superficial illusion of connectivity. Third, the habituation of phubbingbehavior significantly erodes non-verbal communication elements, directly impacting the decline of interpersonal empathy. Fourth, social anxiety in the form of Fear of Missing Out (FoMO) triggers a strong fixation on gadgets, giving rise to the paradoxical condition of being "alone together" in public spaces. This study concludes that the dominance of cyberspace has triggered a crisis of social presence, where adolescents fail to fully allocate their attention and emotions in the real world. Therefore, digital literacy interventions must not merely focus on limiting screen time, but rather be directed towards digital mindfulness practices to restore the emotional and interpersonal communication skills of the younger generation.